2008
DOI: 10.1128/aem.02710-07
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Virulence Genes in Escherichia coli Populations during Manure Storage on a Commercial Swine Farm

Abstract: Confined livestock production farms typically store their wastes prior to land application. Here, we employed three complementary approaches to evaluate changes in the population structure and stability of virulence genes in Escherichia coli during manure storage on a commercial farm that housed healthy swine. Isolates were genotyped by repetitive extragenic palindromic PCR using the BOXA1R primer and evaluated for the presence of selected virulence genes by PCR. Isolates obtained from the manure holding tank … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…Low but detectable culturable levels of bacterial pathogens found earlier in lagoon effluents (McLaughlin et al, 2009) and levels below cultural detection limits found in the present study are similar to results reported by Peu et al (2006), who concluded that fecal bacteria in swine manure effluents applied to field soils were diluted in soil to levels indistinguishable from those of nonmanured soil. Based on studies of E. coli by others (Dubreuil, 2008; Duriez et al, 2008; Kaper et al, 2004; Khac et al, 2006), it is considered possible, but unlikely, because of differences in pathotypes, serotypes, virulence factors, and attenuated virulence potential during manure storage, that E. coli isolated from soils inside and outside the spray fields include virulent human pathogenic strains. All of these enteric pathogens, however, can cause public health problems linked to environmental contamination from field sources that might involve manure or manure‐contaminated soil (Gerba and Smith, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Low but detectable culturable levels of bacterial pathogens found earlier in lagoon effluents (McLaughlin et al, 2009) and levels below cultural detection limits found in the present study are similar to results reported by Peu et al (2006), who concluded that fecal bacteria in swine manure effluents applied to field soils were diluted in soil to levels indistinguishable from those of nonmanured soil. Based on studies of E. coli by others (Dubreuil, 2008; Duriez et al, 2008; Kaper et al, 2004; Khac et al, 2006), it is considered possible, but unlikely, because of differences in pathotypes, serotypes, virulence factors, and attenuated virulence potential during manure storage, that E. coli isolated from soils inside and outside the spray fields include virulent human pathogenic strains. All of these enteric pathogens, however, can cause public health problems linked to environmental contamination from field sources that might involve manure or manure‐contaminated soil (Gerba and Smith, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…The temperature-sensitive C. elegans strain DH26 [fer-15(b26)II] was routinely grown in the presence of E. coli OP50, a uracil auxotroph, using standard practices (52 2 , stx 1 , estIb, estIa, and ast, was determined through multiplex PCR using primers and conditions previously described (8,54,55 The Bingen phylogenetic grouping of each isolate was determined by multiplex PCR screening for the presence of chuA, yjaA, tspE4.C2, and svg as previously described (57,58), using cell lysates prepared by proteinase K digestion. The chuA positive control, ATCC 35381, was purchased from ATCC.…”
Section: Methodsmentioning
confidence: 99%
“…E. coli strains RO8, B44, F107, P16M, AMR-472, and JG280 were used as positive controls for the detection of the virulence genes (1). Selected PCR products were sequenced as described below , and 2 l of DNA extract (7,40). The programs used for multiplex PCR are described by Duriez et al (7).…”
Section: Methodsmentioning
confidence: 99%
“…Selected PCR products were sequenced as described below , and 2 l of DNA extract (7,40). The programs used for multiplex PCR are described by Duriez et al (7). Class 1 integrons were detected using specific primers (TGATGGCGACGC ACGAC and TTGGGCAGCAGCGAAGT) developed with the Primer Premier 5.0 (Premier Biosoft International, Palo Alto, CA) software program (48).…”
Section: Methodsmentioning
confidence: 99%